Pedagogia universitária - Valorizando o ensino e a docência na universidade - Maria Isabel de Almeida; Selma Garrido Pimenta (Universidade do Minho, 2014)
How and under what circumstances training processes regarding how to be a teacher can be developed at a complex university? The paper suggests possible answers to this question, from analysis of the establishment of a teacher education policy at a public university - University of São Paulo, Brazil - whose tradition of research activities overlaps with teaching. To broaden understanding of the undertaken experience, it discusses the meaning of higher education in the context of contemporary university crisis and analyses experiences in institutions that point the importance of teachers to ensure the social significance of university. The analysis is supported by written records and research produced by participants of the process (teachers, managers, doctoral students) as instruments. Considering a conceptual framework of university teaching, the results show some contributions to the field: importance of institutional rooting of policies for pedagogical education of university teachers; inclusion of these policies in the institutional budget; diversity of these educational activities; and enhancement of research findings of teachers about teaching.